The Lender of Last Resort in the European Single Financial Market - Teixeira, Pedro Gustavo (IMF Working Papers; Working Paper ;, 2006)
This paper examines challenges in effectively implementing the lender-of-last-resort function in the EU single financial market. Briefly highlighted are features of the EU financial landscape that could increase EU systemic financial risk. Briefly described are the complexities of the EU's financialstability architecture for preventing and resolving financial problems, including lender-of-last-resort operations. The paper examines how the lender-of-last-resort function might materialize during a systemic financial disturbance affecting more than one EU member state. The paper identifies challenges and possible ways of enhancing the effectiveness of the existing architecture.